Evaluación de herbicidas en el control de malezas de hoja ancha y angosta en el cultivo de Banano (Musa Acuminata) - Murillo De León, Marco Orlando (2022)
The research was carried out at the BASF company, located on the “La María” campusbelonging to the Quevedo State Technical University. The action of commercial herbicides was evaluated in the control and residuality in broad and narrow leaf weeds in the banana crop, different commercial glufosinates of ammonium vs glyphosate and